Passing off Pantalone : representations of Commedia dell’Arte in Aotearoa New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Creative Writing at Massey University, New Zealand, School of Humanities, Media & Creative Communication - Caccioppoli, Paolo (Massey University, 2023)
This thesis explores the question of how the conventions of Commedia dell’Arte are reemployed in Aotearoa New Zealand theatre to make something new. The critical section, comprising half the project, includes four case studies of Aotearoa New Zealand plays in which aspects of the Commedia dell’Arte have been adapted and includes analysis of how the Commedia dell’Arte has allowed for the new exploration of dramatic themes and for the deconstruction of norms inherited from a traditional theatre which has colonisation as its backdrop. The thesis argues that the Commedia dell’Arte, with its capacity for commodification, has been culturally and commercially adapted in Aotearoa New Zealand, in Māori, migrant, and mainstream theatre, such that the use of its marque may no longer be considered to be within the scope of protection that would be afforded to a branded product in the commercial world by the legal tort known as passing off. Understanding how the Commedia dell’Arte methods are employed in the case studies acts as a springboard for discussing some of the practical challenges encountered trying to apply the learnings from the case study analysis to the writing of the creative component, an original playscript Carnival Day. This playscript employs various features of the Commedia dell’Arte, including stock characters, their masks, the lazzi, and grammelot in order to explore their comedic range in a modern Aotearoa New Zealand setting of disease and political uniformity.
Keywords: 360201 Creative writing (incl. scriptwriting)